Supervisory and non-supervisory employees perception towards performance appraisal system in ministry level of Sarawak state civil service - Catherine, Sendon Ngelingkong (2011)
i>erceptions among supervisory and non-supervisory employees toward performance appraisal were examined. The data were obtained from 140 supervisory and non-supervisory employees ranged from Grade 17 to Grade 48 working in six (6) ministries of Sarawak State Civil Service. A questionnaire comprises of 35 items of performance appraisal aspects was used to measure respondents perceptions toward performance appraisal aspect. These items were grouped into five (5) aspects of performance appraisal that are performance evaluation criteria, appraisal interview, disclosure of annual report, purpose of performance appraisal and obstacles of performance appraisal. Respondents were also required to give their recommendation to improve performance appraisal in their organizatioy Frequency analysis shows that 84 or 60% of the respondents were non-supervisory employees and 56 or 40% of the respondents were supervisory employees. Results of means, standard deviations and One-Way-Analysis of Variance (ANOV A) were indicated that supervisory employees 'agree' to majority of items under performance appraisal. These findings show that supervisory employees more satisfied with the performance appraisal as compared to non-supervisory employees. Pearson Correlation Analysis reveals that there are positive and moderate correlations among all performance appraisal aspects. Based on the findings, several recommendations were addressed as a guideline to management to enhance performance appraisal system especially in the ministry level of Sarawak State Civil Service. These recommendations are also applicable to other public sectors. It is hope that this study will fills the gap for the performance appraisal literature in Malaysian Public Sector.